EQUIPMENTS TO SINGLE PHOTON REGISTRATION. PART 1. FEATURES AND POSSIBILITIES OF MULTI-CHANNEL PHOTODETECTORS WITH INTRINSIC AMPLIFICATION. (REVIEW) - O. V. Dvornikov; V. A. Tchekhovski; V. L. Diatlov (Приборы и методы измерений)
The main types of the modern photo detectors applied to single photon registration are analyzed. It is offered to use silicon photomultipliers for production of multi-channel optoelectronic systems with the single photon resolution.